Simulação DNS de fluido não-newtoniano em canal rugoso - Tourinho, Mauricio de Oliveira (2019)
The behavior of a turbulent non-newtonian uid ow in a rough channel is something with a lot unknown yet but it is very important to be known because most of the uids are non-newtonian. On this paper, this behavior was simulated in DNS (Direct Numerical Simulation) for power law at a Reτ = 395, a roughness of type "k" stated by parallelepipeds equally spaced on "X". It was simulated for three uids with indices (n) 1, 0.75 and 0.5, a newtonian and two non-newtonian (pseudopastic), respectively. It were compared to the results from ASHARAFIAN e MANHART (2004), MOSER e MANSOUR (1999) e ANBARLOOEI e FREIRE (2015) following a pre-stated chronology so the results found on the simulation would be properly validated, this precaution was done because it was not found any publication on this matter. After it was done the results apparently are in consistency with the articles, showing that the results seems correct.